Perancangan OpenChart Sebagai Solusi Visualisasi Data untuk Optimalisasi Penjualan Online Kerajinan Tangan di Kota Payakumbuh - Kusniati, Rani; Annas, Firdaus; Desriana, Desriana (JOVISHE : Journal of Visionary Sharia Economy, 2024)
The development of information and communication technology, especially the internet, has opened up new opportunities for crafters in Payakumbuh City as well as other micro, small and medium enterprises (MSMEs) to market their merchandise online. However, many MSMEs still face difficulties in utilising internet-based sales data to improve their business strategies. Therefore, this research aims to develop OpenChart as a data visualisation tool that can help handicraft MSMEs in Payakumbuh increase online sales. This research uses the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model combined with a Research and Development (R&D) approach. The ADDIE stages include needs analysis, system design, application development, implementation, and evaluation. In the needs analysis stage, challenges faced by MSMEs in utilising sales data were identified. Then, the OpenChart system was designed and developed to provide an easy-to-understand sales data display. Based on the research results, OpenChart allows Payakumbuh Handicraft MSMEs to view sales data in real-time. With this feature, businesses can analyse sales trends, identify the most popular products, and optimise their marketing strategies more effectively, thus increasing business competitiveness in the digital era. Translated with DeepL.com (free version)